Simulation of the Frequency Doubled Nd:YAG Laser Effect on the Retina - Nabi, T.A. Abdul; Mohammed, H. H.; Mohammed, K.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was conducted with a view to determine whether focal laser therapy results in avisual recovery and regression of macular odema in patients with non-proliferative diabetic maculopathy. A Frequency doubled Nd:YAG laser was used for the treatment of diabetic maculopathy. For several has been studied and the treatment results were discussed. The study evaluates 14 eyes of 8 diabetic patients. Mathematical model of the laser interaction with the retinal tissue is demonstrated and analysis results are explained and compared with the recent experimental and mathematical models . It has been shown that the laser treatment of the retinal diabetic macolapathy , a disease that reduces vision significantly , would stop the extension of such adisease in many cases , while it improves the visual acuity for the other cases, mathematical model put forward is shown to be consistent with the recent experimental and theoretical models .Calculation results of the laser retinal energy density as a function of the spot size are studied and compared with the corresponding features of a typical laser damage which is based on athermal damage.